Transabdominal ultrasonography: A non-invasive method for diagnosing vaginal atrophy. Issue 4 (December 2020) - Kanmaz, Ahkam Göksel; İnan, Abdurrahman Hamdi; Beyan, Emrah; Budak, Adnan; Töz, Emrah; Alan, Murat; Özeren, Mehmet
Objective: Genitourinary syndrome of menopause is a definition of all symptoms caused by hypoestrogenemia in menopausal age and one of the most common symptoms is vaginal atrophy. The diagnosis methods which are used for vaginal atrophy may be painful. A novel method total vaginal thickness and total mucosal thickness measuring could be determine vaginal atrophy. Material and methods: This is a prospective case–control study involving 60 women in each group of 120 patients. One of the groups is comprised postmenopausal, histopathologically diagnosed vaginal atrophic women and the other group comprised 24–35 aged women who were no symptoms of vaginal atrophy and vaginal swab samples are not compatible with vaginal atrophy. All women who participated in the study underwent transabdominal ultrasound and total vaginal thickness and total mucosal thickness were measured. Results: Total vaginal thickness and total mucosal thickness were found lower in the postmenopausal group compared to premenopausal women ( p  = 0.005 and p  = 0.07, respectively). The cutoff value was determined as 8.55 mm for total vaginal thickness and 1.52 mm for total mucosal thickness, and the diagnostic power of these values is a specificity of 88.89% (95% confidence interval: 51.75–99.72%) and a ppv of 92.86% (95% confidence interval: 66.53–98.84%) for total vaginal thickness and a specificity of 80.95% (95% confidence interval: 58.09–94.55%) and a ppv of 89.47% (95% confidence interval: 71.10–96.71%) for total mucosal thickness. Conclusion: Vaginal atrophy is a painful symptom for menopausal women and the diagnostic methods may be invasive and painful too. Total vaginal thickness and total mucosal thickness measuring with transabdominal ultrasound could be an alternative method for diagnosis and treat vaginal atrophy easily.